Teaching Polymer Chemistry: Revisiting the Syllabus - Hamaide, Thierry; Holl, Yves; Fontaine, Laurent; Six, Jean-Luc; Soldera, Armand (Scientific Research, 2012)
As anyone who has taught polymer chemistry to undergraduate students might already appreciate, we are faced with inherent difficulties in clearly communicating the subject matter due its interdisciplinary character. This paper is thus aimed at proposing a new educational plan to teach this fundamental course in order to overcome some inherent obstacles. It is especially devoted to professors in charge of teaching a first course in polymer chemistry. We intend to emphasize polymerization by beginning with the simplest chemical pathway, namely the living anionic polymerization. In addition, some pedagogical difficulties are outlined all along this paper. This novel and distinct way to teach polymer chemistry makes the students with a background in organic chemistry more equipped to face difficulties arising from the introduction of new concepts.
Keywords: Teaching Polymer Chemistry; Chain Polymerization; Step-Growth Polymerization; Polycondensation; Polyaddition